Creating knowledge management with the role of leadership and organizational culture - Pringgabayu, Dematria; Ramdlany, Dany Muhammad Athory (Journal of Entrepreneurship, Business and Economics, 2017)
The research was conducted to determine whether the leaderhsip and organizational culture have positive and significant impact on knowledge management at State Owned-Port Company. This study has three variables, namely the leaderhsip and organizational culture as an independent variable and knowledge management as the dependent variable. Data obtained from interviews and questionnaires were distributed to the employee population at State Owned-Port Company This research method uses descriptive method and verification method. Data processing is performed using path analysis. The result of this study indicate that leadership has a significant influence 12,8% on knowledge management and organizational culture has a significant influence 26,7% on knowledge management at State Owned-Port Company. Simultaneously, leadership and organizational culture have total influence 0,958 on knowledge management at State Owned-Port Company. Research paper Keywords: Leadership, Organizational Culture, Knowledge Management Reference to this paper should be made as follows: Pringgabayu, D., & Ramdlany, D. M. A. (2017). Creating knowledge management with the role of leadership and organizational culture, Journal of Entrepreneurship, Business and Economics , 5 (2), 147–171.